Análisis de la apertura comercial en el sector agrícola de Michoacán - Contreras Valencia, Yadira Janette (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
The commercial opening of the agricultural sector in Mexico is a very debated topic; agreements and disagreements arise to the moment to be about giving a solution to the more and more precarious situation of the Mexican field. Mexico traffics, in an abrupt way, of a system extremely protective (the call System of Substitution of Imports, ISI) to be one of the economies more open of the world. The transition is carried out in less than two government sexenios. It begins with Miguel from Madrid in 1980 and, it reaches the peak in 1994, when the Treaty of Free Trade of North America is signed. During this time of structural changes in the public politicians, the Mexican field, faces reformations that represent an important retirement of the state of the activities that has to do with the regulation of the economy, as well as the dismantlement of the system of guarantee prices, and the closing of public several companies at the hands of private. In the state of Michoacán, the national situation is reflected. The entity conforms to of small and big producers, the first many times considered without productive potential; it has influenced so that the access to the credit is polarized, leaving desprotegidos to this type of smaller producers.

La apertura comercial del sector agrícola en México es un tema muy debatido; acuerdos y desacuerdos surgen al momento de tratar de dar una solución a la situación cada vez más precaria del campo mexicano. México transita, de manera abrupta, de un sistema sumamente proteccionista (el llamado Sistema de Sustitución de Importaciones, ISI) a ser una de las economías más abiertas del mundo. La transición se lleva a cabo en menos de dos sexenios de gobierno. Inicia con Miguel de la Madrid en 1980 y, alcanza la cúspide en 1994, cuando se firma el Tratado de Libre Comercio de Norteamérica. Durante esta época de cambios estructurales en las políticas públicas, el campo mexicano, se enfrenta a reformas que representan un importante retiro del estado de las actividades que tiene que ver con la regulación de la economía, así como el desmantelamiento del sistema de precios de garantía, y el cierre de varias empresas públicas a manos de privados. En el estado de Michoacán, se ve reflejada la situación nacional. La entidad se conforma de pequeños y grandes productores, los primeros muchas veces considerados sin potencial productivo; ha influido para que el acceso al crédito se vea polarizado, dejando desprotegidos a este tipo de productores más pequeños.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2010-0007; Mercantilismo; TLCAN; Políticas públicas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/941